1976
DOI: 10.1021/jm00234a006
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemical studies of adrenergic drugs. Optically active derivatives of imidazolines

Abstract: The synthesis of (R)-(+)-4-methyl-2-(1-naphthylmethyl)imidazoline hydrochloride (2) and (S)-(-)-4-methyl-2-(1-naphthylmethyl)imidazoline hydrochloride (3) is presented. The synthesis involves the preparation of (R)-(+)- and (S)-(-)-1,2-diaminopropane dihydrochloride and then allowing the appropriate diaminopropane to react with ethyl 1-naphthyliminoacetate hydrochloride in the presence of triethylamine. The parent compound, naphazoline, is a potent alpha-adrenoreceptor agonist (-log ED50 = 7.22), whereas the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

1977
1977
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 4 publications
0
21
0
Order By: Relevance
“…We have previously reported that the trifluoromethylimidazole derivative la lowered mean arterial blood pressure in the spontaneously hypertensive rat (SHR) and exhibited vasodilating and /^-selective adrenoceptor antagonism in the dog. 6 The observed selectivity was on the order of that seen with practolol (Table II). Variation of the trifluoromethyl group of la yielded specific examples that demonstrated enhanced ß selectivity (compounds ld-f, Table II).…”
Section: Resultsmentioning
confidence: 86%
“…We have previously reported that the trifluoromethylimidazole derivative la lowered mean arterial blood pressure in the spontaneously hypertensive rat (SHR) and exhibited vasodilating and /^-selective adrenoceptor antagonism in the dog. 6 The observed selectivity was on the order of that seen with practolol (Table II). Variation of the trifluoromethyl group of la yielded specific examples that demonstrated enhanced ß selectivity (compounds ld-f, Table II).…”
Section: Resultsmentioning
confidence: 86%
“…In the naphazoline series, both substituents decrease intrinsic activity dramatically to the point at which these compounds become competitive antagonists of alpha-1 adrenergic receptors (Table 9). No stereoselectivity is found to exist between the enantiomers of either the methyl-or benzyl-substituted naphazoline derivatives (Fuder et al, 1981;Hsu et al, 1980;Miller et al, 1976). The same qualitative effects are observed when these substitutions are made in catechol derivatives of the imidazolines (Table 9).…”
Section: Imidazolinesmentioning
confidence: 92%
“…Vicinal diamines are important ligands for metal complexes [1][2][3][4][5] and useful substrates for heterocyclic compound synthesis. [5][6][7][8] 1,2,4-Triaminobutane derivatives were previously applied for preparation of dicarboxylic acids bis(1,2,4-triaminebutane-N 4 )amides with two vicinal diamines. These compounds were used for synthesis of bis[platinum(II)] complexes capable of interstrand-DNA binding.…”
mentioning
confidence: 99%
“…(2S)-N 4 -Benzyloxycarbonyl-2,4-diaminobutanoic acid methyl ester 16 was prepared under standard reaction conditions and converted into (2S)-N 4 -benzyloxycarbonyl-2,4-diaminobutanamide (3), applying the reported amino acids amides preparation method. 7,8 Then, (2S)-N 4 -benzyloxycarbonyl-2,4-diaminobutanamide (3) was reduced with diborane in THF (diborane selectively reduces amides 2,7,8,[19][20][21][22][23][24][25] in the presence of alkoxycarbonyl groups [22][23][24][25] ) yielding the selectively N 4 -protected (2S)-1,2,4-triaminobutane derivative 4. The diborane reduction of 3, however under reported amino acids reductions conditions, 7,8 gave a complex mixture of various reaction products.…”
mentioning
confidence: 99%